A numerical model for predicting the aerodynamic characteristics of propelling nozzles - Al-Akam, Aws A.; Nikolaidis, Theoklis; MacManus, David G.; Goulos, Ioannis (International Society for Air Breathing Engines (ISABE), 2019)
It is essential to predict the exhaust-system performance of the aero-engine during the design stages as it plays a critical role in the engine components matching. In addition to this, it has an impact on the overall engine performance. Consequently, it is important to model the complex flow features around the exhaust system accurately in order to capture the flow characteristics. Computational Fluid Dynamics (CFD) alongside with low-order models can play a central role in the design and performance assessment of the propulsion system. This paper aims to explore the suitability of a numerical model, boundary conditions, and the employed mesh topology in computing a propelling nozzle performance. The current work is a first step towards building a module to assess a wide range of nozzle configurations at the preliminary design stages. A single-stream and plug-nozzle propelling nozzle were simulated for this purpose. For the single-stream nozzle, the simulations were run at various flight conditions and different geometrical features. For both nozzle configurations, a comparison between the effectiveness of six turbulence models to capture the nozzle flow features is presented. The validated module is then used to assess the impact of the bypass flow and the plug half-angle on the performance of the core nozzle for a dual-stream nozzle configuration. The calculated nozzle efficiencies are lower than the experimental data for both nozzle types, with a maximum difference of single-stream nozzle efficiency ≈ - 3.29% at NPR = 1.83 and by -0.84% at NPR = 3.88 and for the plug nozzle with -1.05% at NPR 2.64 and across a range from -0.46% to -0.68% between NPR = 3.14 to 5.3. The application of RANS k-ω SST turbulence model showed the best results as compared with the standard k-ε, RNG k-ε, realizable k-ε, and Spalart-Allmaras models in simulating the propelling nozzles aerodynamics. Generally, the results show the strength and the weakness of the numerical module in simulating the nozzle flow features and predicting its performance. Moreover, the Fan Nozzle Pressure Ratio (FNPR) and the plug half-angle (ω) has a noticeable impact on the overall and core nozzle performance. Moreover, the combined impact of both parameters has a noticeable impact on the propelling nozzle performance.
Keywords: Propelling nozzle; nozzle aerodynamics; thrust coefficient; plug nozzle